A interação docente na produção de textos nos anos finais do ensino fundamental em contexto de ensino híbrido - Morais, Virgínia Maria de (2022)
Teacher interaction in the procedural teaching of written texts plays a fundamental role. Starting from this conception and the practices and principles that lead to the development of writing in Elementary School, the guiding thread of this research originates. However, the coronavirus crisis and the temporary suspension of face-to-face school activities imposed the need to explore the subject of study from the perspective of blended learning. Based on these considerations, this master's thesis aimed to examine in the pedagogical practices of teachers, the concepts about interaction present in their work of textual production with students of the final years of Elementary School in the context of hybrid education. This investigation is based on an interactionist teaching and learning perspective, on the conception of pedagogical intervention (VYGOTSKY, 1999) and on the concept of constructive interaction (CALKINS; HARTMAN; WHITE, 2008) evidenced in the methods applied by teachers when they define what to teach and how to do it in text writing and rewriting activities. Another theoretical axis that underlies this work refers to the studies that interpret the teaching actions in the teaching of writing (PASSARELLI, 2004); (BRONCKART, 2006) and that refer to theoretical conceptions in pedagogical practices (BITTENCOURT et al, 2015). In this bias, this research is characterized as a diagnosis of the investigated reality, in a qualitative approach, organized from the following data collection instruments: questionnaires; semi-structured interview with Portuguese language teachers; observation of classes and student texts. The investigation context is of a private school that uses online pedagogical practices in the teaching and learning processes in the hybrid modality. The results of this study indicate that, in terms of written language competence, teacher interaction is configured as a process of (re)construction of knowledge with which the observed students assimilate the contents of writing in a hybrid teaching context. Thus, in view of the data collection and mapping of the relevance of teacher interaction in learning modalities, this research points out that the pedagogical practices found were problem-based learning, research in textual practice, dramatization, the inverted classroom and the Hybrid Teaching itself. These pedagogical practices, combined in person and online, were considered as interactive skills for the development of multiliteracies in students in virtual learning contexts.